2022
DOI: 10.3390/metabo12040297
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix in Heart Disease: Focus on Circulating Collagen Type I and III Derived Peptides as Biomarkers of Myocardial Fibrosis and Their Potential in the Prognosis of Heart Failure: A Concise Review

Abstract: Accumulating evidence indicates that two major proteins are responsible for the structural coherence of bounding cardiomyocytes. These biomolecules are known as myocardial fibrillar collagen type I (COL1) and type III (COL3). In addition, fibronectin, laminin, fibrillin, elastin, glycoproteins, and proteoglycans take part in the formation of cardiac extracellular matrix (ECM). In physiological conditions, collagen synthesis and degradation in human cardiac ECM are well-regulated processes, but they can be impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 90 publications
1
30
0
Order By: Relevance
“…Myocardial fibrosis features by changes in ECM. Previous studies on ECM and myocardial fibrosis mainly focused on collagen types I and collagen type III, which were used as non-invasive monitoring methods for tissue and organ fibrosis ( 6 , 13 ). Serum LN is an important part of ECM, which was first discovered in mouse tumor basement membrane by Timple and other researchers in 1979 ( 14 ), serum LN is one of the largest non-collagenous glycoproteins in the basement membrane and plays a key role in fibrosis formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial fibrosis features by changes in ECM. Previous studies on ECM and myocardial fibrosis mainly focused on collagen types I and collagen type III, which were used as non-invasive monitoring methods for tissue and organ fibrosis ( 6 , 13 ). Serum LN is an important part of ECM, which was first discovered in mouse tumor basement membrane by Timple and other researchers in 1979 ( 14 ), serum LN is one of the largest non-collagenous glycoproteins in the basement membrane and plays a key role in fibrosis formation.…”
Section: Discussionmentioning
confidence: 99%
“…Laminin (LN) is a vital component of ECM, which has significant biological functions, including adhesion, translocation, cell differentiation, cell growth, and inflammatory response (4). Many studies have shown that LN is closely related to the process of myocardial fibrosis (5)(6)(7). The 2022 AHA/ACC/HFSA guidelines (8) divide HF into four stages (stages A-D) according to HF progression, which objectively reflects the clinical progress of CHF.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, gelatin is used due to its high resemblance to collagen [ 112 ], while fibronectin is a binding protein in tissues throughout the body, including the heart [ 113 ]. With this, it was evidenced that the functionalization of chitosan with hydroxybutyl and the addition of fibronectin and gelatin allowed for the construction of structures with aligned pores, thus generating an oriented and united cardiac tissue with similar biological properties to the natural myocardial tissue [ 111 ].…”
Section: Scaffolds For Cardiac Tissue Regenerationmentioning
confidence: 99%
“…The production and degradation of ECM are commonly regulated by MFs, together with macrophages and other cell types ( Yap et al, 2023 ), such as CFs produce matrix metalloproteinases (MMPs) degrading collagens and tissue inhibitors of MMPs (TIMPs) inducing collagen synthesis ( Nikolov and Popovski, 2022 ). There are four major ECM-associated peptides: the N-terminal propeptide of collagen type III (PIIINP) (indicating collagen III synthesis), the C-terminal telopeptide of collagen type I (ICTP) (indicating collagen I degradation), N-terminal propeptide of collagen type I (PINP), and C-terminal propeptide of collagen type I (PICP) (both PINP and PICP indicate collagen I synthesis) ( Nikolov and Popovski, 2022 ). A recent study finds that the single mutation of thioredoxin-interacting protein cysteine 247 reduces collagen I α1 chain in MI mice ( Nakayama et al, 2021 ).…”
Section: Pathophysiology Of Post-mi Cardiac Fibrosismentioning
confidence: 99%